Building web-based library catalog using open source library system - Mansor, Yushiana; Awang Abu Bakar, Normi Sham (s.n, 2012)
The library automation marketplace is currently witnessing aggressive movements towards open source environment. This paper showcases the progress of two projects using open source library solutions in enhancing access to the collections at the Hamzah Fansuri Resource Centre, Kulliyyah of ICT, IIUM. The first project involved using the Koha library management system, and the second, using Dspace for digital library development. Several issues related to open-source project management were experienced, particularly in the context of a small-sized library with minimal staff support. The fast movement towards digital library environment has resulted into mushrooming number of institutional repositories especially in academic, educational, and research institutions. At the same time, discovering resources in the various repositories is time-consuming and tedious requiring users to become familiar with the various digital repositories set up. In addition, it is typical that within an organization, repositories have been developed in isolation using different practices and implementation design. Harnessing the full potential of intellectual capital of the organizational community becomes problematic as federated search across the disparate databases is not possible due to several factors including interoperability. Consequently, interoperability has since becomes an important design consideration in networked library development. The paper also reports on the feasibility of harvesting organizational repositories using open source